Guided university debate: Effect of a new teaching-learning strategy for undergraduate nursing students. (December 2017) - Arrue, Marta; Unanue, Saloa; Merida, David
Abstract: Background: A number of studies have shown that the traditional lecture suffers from limitations in the development of many important competencies such as reasoning ability for nursing professionals. Objectives: In view of this issue, the authors present a promising alternative to the traditional lecture: the Guided University Debate (GUD). With regard to this aim a teaching-learning sequence of schizophrenia is described based on the GUD. Next, the improvement in the argumentative and declarative knowledge of the students who have participated in the said methodology is demonstrated. Methods: Quasi-experimental study with pre-test and post-test design to measure differences in the improvement of declarative and argumentative knowledge. To determine if there is a statistically significant difference in the score obtained in the pre-test and in the post-test score a parametric t -tests was carried. 64 students participated in the study. Implementation of the study took place during the 2015–2016 academic year in the third year of the Nursing undergraduate degree course in the University of the Basque Country (UPV/EHU) as part of the Mental Health class. Results: The results showed a statistically-significant improvement in the students' scores for all learning outcomes analysed: Identifies symptoms of schizophrenia ( p ≤ 0.001), identifies the nursing interventions ( p ≤ 0.001), provides a rationale for nursing interventions (p ≤ 0.001) and provides evidence of nursing interventions (p ≤ 0.001). That is, the declarative and argumentative capacity of the group improved significantly with the Guided University Debate methodology. Conclusions: Although the teaching design feasibility and outcomes may vary in different contexts, based on this studies' positive outcome, the authors call today's educators to be able to use GUD as a teaching method. Highlights: The research indicates that the Guided University Debate is a satisfactory teaching-learning strategy: Declarative knowledge (memorizing) is ensured by this kind of instruction. A significant high percentage of students have developed argumentative competence. The GUD is based on: a closed question, a public debate and teachers mentoring.